Project Planning Analysis with the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT): Study on the Development of Facilities and Infrastructure of SMK Negeri 1 Garut (DOOM) - Arif Kuswanto; Olivia Tahira Shalshabila (Jurnal Indonesia Sosial Teknologi, 2025)
Success in implementing a project often hinges on thorough planning and effective control. This study examines the infrastructure development project at SMK Negeri 1 Garut (DOOM), applying the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT) to estimate project completion time, costs, probability, and potential planning alternatives. The goal is to achieve maximum efficiency and project success. The research began by determining the activities, their sequence, and duration using the PERT and CPM methods, with POM QM as the data processing tool. Based on the PERT method, the estimated project duration is 128 days with a 50% probability. The critical path, identified through the CPM method, includes activities B through P and predicts a project time of 116 days with a 0.13% probability. Additionally, Crashing the project reduces the time to 97 days, with a minuscule probability of 3.095359E-15. The probability of meeting the contract deadline of 126 days is 31%. To achieve a 95% probability, the project time extends to 130 days with an acceleration cost of IDR 2,575,898,910.73. The study suggests that when making addendums, companies should not only focus on cost changes but also consider adjustments to project timelines to meet the expected deadlines. It is recommended that companies incorporate CPM and PERT as alternative planning methods to select the most optimal cost-effective approach for project acceleration, thereby minimizing the risk of financial losses.